Identyfikacja procesów jako stadium przygotowawcze w projektowaniu usprawnień - Stabryła, Adam (Process Identification - an Introductory Analysis in Designing Improvements, 2009)
The objective of the paper is to present the cycle of process identification for the needs of designing improvements. Process identification involves a description and interpretation of the structure and functioning of processes focusing on the following phases: the selection of identification methods, the identification of the investigated system, the scope of process formalization, process configuration as well as the identification of external threats and process deficiencies. The paper discusses the phases of process identification: the selection of identification techniques, the identification of the examined system and the scope of process formalization, the identification of process configuration as well as external threats and process deficiencies. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 207-213